K, MG, TI AND CA ISOTOPIC COMPOSITIONS AND REFRACTORY TRACE ELEMENT ABUNDANCES IN HIBONITES FROM CM AND CV METEORITES: IMPLICATIONS FOR EARLY SOLAR SYSTEM PROCESSES - Sahijpal S.; Goswami J.N.; Davis A.M. (My University, 2000)
Potassium and magnesium isotopic compositions of hibonites from the Murchison (CM) and Allende (CV) meteorites are determined by an ion microprobe to look for possible presence of the short-lived nuclides 41Ca and 26Al at the time of their formation. Abundance anomalies in the neutron-rich isotopes 50Ti and 48Ca as well as REE and additional refractory trace element abundances have also been determined to infer a plausible formation environment of the hibonites in the early solar system. The results obtained in this study suggest a widespread distribution of the short-lived nuclide 41Ca in the early solar system. Observation of correlated presence of the two short-lived nuclides 41Ca and 26Al on a microscopic scale in refractory hibonites and silicates from CM and CV meteorites suggests these nuclides to be cogenetic and support a stellar source for these and several other short-lived nuclides in the early solar system. Moderate to high enrichments in the neutron-rich isotopes 50Ti and 48Ca are seen in some of the analyzed hibonites. Our data for radiogenic and stable isotopic anomalies as well as refractory trace element abundance patterns in isolated CM hibonites with platelet morphology show trends similar to those reported earlier. They are devoid of 41Ca and 26Al, show large enrichment in 50Ti and 48Ca and have typical Group III REE patterns. However, hibonites present within hibonite-spinel inclusions show variations in their REE patterns. One of them shows the normally expected Group II REE pattern, while another has an ultrarefractory REE pattern and a third has affinities towards platelet hibonites that appear to suggest a link between these two groups of hibonites with distinct morphological characteristics. We propose a new model to explain the absence of the short-lived nuclides 41Ca and 26Al in some of the hibonites, whose REE abundance patterns and stable isotopic anomalies suggest that they are some of the first solar system solids, assuming a stellar origin for these nuclides. We attribute this absence to the very early formation of these hibonites near the central region of the collapsing protosolar cloud prior to the arrival of the short-lived nuclides injected into the cloud from a stellar source.